A systematic comparative study of the efficient co-catalyst-free photocatalytic hydrogen evolution by transition metal oxide nanofibers. (6th September 2018) - Yanalak, Gizem; Aljabour, Abdalaziz; Aslan, Emre; Ozel, Faruk; Patir, Imren Hatay
Abstract: The efficiencies of a series of hydrogen evolving catalysts based on metal oxide nanofibers (NiO, Co3 O4, Mn3 O4 ) are investigated for the photocatalytic hydrogen evolution from water without using any co-catalyst under the visible light irradiation by using triethanolamine (TEOA) as an electron donor and Eosin-Y (EY) dye as a photosensitizer. It is found that the photocatalytic hydrogen evolution activities follow the order as: Mn3 O4 3 O4 <NiO (196 μmolg −1 h −1, 5552 μmolg −1 h −1, 7757 μmolg −1 h −1, respectively). Moreover, the catalytic behavior of these nanofibers on the hydrogen production has been also compared to bulk forms of NiO, Co3 O4 and Mn3 O4 by producing hydrogen 937 μmolg −1 h −1, 901 μmolg −1 h −1 and 135 μmolg −1 h −1, respectively. The nanofiber structures demonstrated much higher photocatalytic activity than bulk forms due to the effect of the increased surface to volume ratio deduced from the fibrous character. The photocatalytic plausible pathway for the hydrogen production is also discussed. Graphical abstract: Metal oxide nanofibers (NiO, Co3 O4, Mn3 O4 ) have been used as efficient catalysts for the photocatalytic HER under the visible light irradiation by using triethanolamine (TEOA) as an electron donor and Eosin-Y (EY) dye as a photosensitizer in the absence of co-catalysts. Image 1 Highlights: Electrospinning technique is applied for the synthesis of the metal oxide nanofibers (MONs). The ease of the synthesis protocol enables the production of highly stable nanofibers. MONs have been used as heterogenous catalysts for the photocatalytic HER. The rate of hydrogen generation follows the order as: Mn3 O4 3 O4 <NiO. The HER activities of nanofibers are also compared to bulk forms of these materials.